Pengaruh Label Halal terhadap Keputusan Pembelian Konsumen Muslim pada Produk Almaz Fried Chicken Kambang Iwak - Mulyani Rizki; Yunita Azaria (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
Modern lifestyles have transformed the consumption patterns of urban communities in Indonesia, who now tend to prefer fast food due to the demands of a fast-paced lifestyle. This phenomenon is accompanied by growing awareness among Muslim consumers regarding the importance of halal certification. This study aims to explore in greater depth the extent to which halal labelling influence the purchasing decisions of Muslim consumers, specifically regarding Almaz Fried Chicken products in the Kambang Iwak area of Palembang City.This study employs a quantitative approach using a questionnaire as the primary instrument. Data were collected from 96 respondents selected via accidental sampling. The variables examined include halal labelling (X) and purchasing decisions (Y). Data analysis was conducted comprehensively, covering validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing via t-tests and F-tests to examine the influence of variables partially The research results show that the halal label has a positive and significant influence on purchasing decisions, partially. The halal label is a crucial factor in providing Muslim consumers with confidence in choosing products. This finding confirms that, in the context of Muslim consumers, the halal aspect is highly influential in determining purchasing decisions.